2016
DOI: 10.1109/tit.2016.2615632
|View full text |Cite
|
Sign up to set email alerts
|

On the Capacity of Vector Gaussian Channels With Bounded Inputs

Abstract: Abstract-The capacity of a deterministic multiple-input multiple-output (MIMO) channel under the peak and average power constraints is investigated. For the identity channel matrix, the approach of Shamai et al. is generalized to the higher dimension settings to derive the necessary and sufficient conditions for the optimal input probability density function. This approach prevents the usage of the identity theorem of the holomorphic functions of several complex variables which seems to fail in the multi-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…As a matter of fact, this phenomena that the optimal input distribution lies on finitely many concentric spheres remains true for any n ≥ 2, cf. [4], [5] and [6].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, this phenomena that the optimal input distribution lies on finitely many concentric spheres remains true for any n ≥ 2, cf. [4], [5] and [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, only few antenna elements are required, for the hit in data rate to become negligibly small. In fact, it can be shown that for any fixed SNR in a MIMO system with bounded inputs, there exist a threshold for the number of antennas, beyond which the amplitude component of the vector signal does not contribute to mutual information [23]. The findings of Fig.…”
mentioning
confidence: 86%
“…From the duality of channel coding and universal source coding (Chapter 13 in [20]), the solution of Q Y in (41) is the induced output distribution of the capacity-achieving distribution of this channel. The solution to this problem has been investigated in [24] and [25] and it has been shown that the support of the capacity-achieving distribution is a finite set of hyper-spheres with mutual independent phases and amplitude in the spherical domain. A uniform distribution on a single sphere is optimal as R √ n → 0 has been shown in [24].…”
Section: A Converse Bounds Under Maximal Power Constraintmentioning
confidence: 99%
“…The solution to this problem has been investigated in [24] and [25] and it has been shown that the support of the capacity-achieving distribution is a finite set of hyper-spheres with mutual independent phases and amplitude in the spherical domain. A uniform distribution on a single sphere is optimal as R √ n → 0 has been shown in [24]. In general case when R = √ nP and R/ √ n = √ P is a constant, the uniform distribution of the surface of the sphere is not optimal.…”
Section: A Converse Bounds Under Maximal Power Constraintmentioning
confidence: 99%